Kendala pembangunan PLTSa dalam tinjauan kriminologis - Putri, Misliharira Shaumi; Puteri, Ni Made Martini (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The development of Waste Power Plants (PLTSa) is an alternative waste management that can significantly reduce waste volume, especially in 12 areas with large amounts of waste. However, to this date, the development of PLTSa has faced obstacle, despite numerous regulations issued to accelerate its implementation in these areas. The issue of waste accumulation is urgent as it can have adverse effects on the environment and community’s well-being. Because it is regarded as a form of environmental pollution, the accumulation of waste become an environmental crime. Method: From a criminological perspective. Findings: Actions that are causing delays in PLTSA development can be categorized as environmental crimes due to subjective deviations and actions that objectively violate existing regulations. Conclusion: With the urgency of rising waste volumes, there is a need for reinforcement of regulations regarding of the implementation of PLTSa development, including the Presidential Regulation No. 35 of 2018, which pertains to accelerating the construction of PLTSa developments.